A porphyrin and some phthalocyanines conjugated to graphitic carbon nitride and manganase ferrites nanoparticles and supported on electrospun nanofibers for photosono-degradation of organic pollutants - Mkhondwane, Siphumelele Thandokwazi (Rhodes University, 2025)
This thesis reports on the synthesis, characterization and application of the zinc phthalocyanines (Pcs) and porphyrin in degradation of organic pollutants using photo- (visible light), sono- (ultrasound) and photosono-catalytic processes (combined visible light and ultrasound). To enhance the physicochemical properties, the Pcs and porphyrin were conjugated with nanoparticles (g-C₃N₄ nanosheets, g-C₃N₄ quantum dots and MnFe₂O₄ nanoparticles) through covalent linkage. To enhance catalytic stability and usability, the Pcs porphyrin and conjugates were supported on electrospun nanofibers. The electrospun nanofibers that were used as supports were TiO₂ and ZnO nanofibers. The Pcs were supported on TiO₂ nanofibers using covalent linkage and physical adsorption. The effect of the symmetry of the Pcs, number of the oxygen species and the mode of support on electrospun nanofibers were investigated by comparing their catalytic efficiencies in degradation of organic pollutants. The pollutants that were studied were Rhodamine 6G and 2,4-dichlorophenol. The catalytic efficiencies of the conjugate of MnFe₂O₄ nanoparticles were also studied. The catalytic efficiencies of the conjugate of g-C₃N₄ nanosheets, g-C₃N₄ quantum dots could not be investigated because these conjugates were soluble in water. The results showed that the asymmetric Pcs were more catalytically active than their symmetrical analogous. The Pcs with higher number of oxygen species were more catalytically active than the Pcs with lesser number of oxygen species. The conjugates of the MnFe₂O₄ nanoparticles were more active than pristine Pcs and the conjugates of g-C₃N₄ nanosheets, g-C₃N₄ quantum dots had improved photophyiscal properties. The functionalized TiO₂ fibers through conjugate linkage with the Pcs were more catalytically active than functionalized TiO₂ fibers through physical adsorption. The functionalized TiO₂ fibers and ZnO fibers with the conjugates of Pcs and nanoparticles were more active than the functionalized fibers with Pcs only. The photosono-catalytic process was more active than photo- and sono-catalytic processes alone. The investigation of the reactive species revealed that photocatalytic processes is driven by singlet oxygen while sono- and photosono-catalytic processes are driven by singlet oxygen and hydroxide radicals.
Keywords: Porphyrins (http://id.loc.gov/authorities/subjects/sh85105022); Phthalocyanines (http://id.loc.gov/authorities/subjects/sh85101459); Nanoparticles (http://id.loc.gov/authorities/subjects/sh85089689); Photodegradation (http://id.loc.gov/authorities/subjects/sh2007001664); Pollutants (http://id.loc.gov/authorities/subjects/sh85104528); Chemistry